Distinct kainate receptor phenotypes in immature and mature mouse cerebellar granule cells - Smith, T Caitlin (Blackwell Science Inc, 1999)
1. Although glutamate receptors have been shown to be involved in neuronal maturation, a developmental role for kainate-type receptors has not been described. In addition, the single-channel properties of native kainate receptors have not been studied in situ. We have characterized the electrophysiological properties of native kainate receptors of granule cell neurons at two distinct stages in postnatal development, using whole-cell and outside-out patch-clamp recordings in acute cerebellar slices. 2. Kainate-type currents were detected in both immature and mature granule cells. However, noise analysis showed that the apparent unitary conductance of kainate-type channels is significantly higher in proliferating than post-migratory granule cells. The conductance and rectification behaviour of the channels in immature granule cells indicate that they contain unedited GluR5 and GluR6 subunits and are likely to be calcium permeable. 3. Single-channel kainate-type currents were observed in outside-out patches from proliferating granule cells in the external germinal layer. The kinetic behaviour of kainate receptors in immature cells was complex. Openings to multiple conductance levels were observed, although our analysis indicates that the channels spend most of their open time in a 4 pS state.